Occurrence and profiles of lipophilic toxins in shellfish harvested from Argentina. (August 2015) - Turner, Andrew D.; Goya, Alejandra B.
Abstract: The presence of phytoplankton responsible for the production of lipophilic marine biotoxins is well recognised throughout parts of South America. To date, the quantitation of lipophilic toxins in Argentinean shellfish has been limited to select and highly focussed geographical studies. This work reports the analysis for lipophilic marine biotoxins in shellfish harvested across five regions of Argentina between 1992 and 2012. LC-MS/MS analysis was used for the quantitation of all regulated lipophilic toxins. High concentrations of okadaic acid group toxins were quantified, with a clear dominance of the parent okadaic acid and more than 90% of the toxin present as esters. Results showed DSP toxins in shellfish from the Buenos Aires Province during 2006 and 2007, earlier than previously described. There was also strong evidence linking the presence of okadaic acid to human intoxications. Other lipophilic toxins detected were yessotoxin, pectenotoxin-2 and 13-desMeC spirolide. With evidence published recently for the presence of azaspiracid producers, this work reports the detection of low concentrations of azaspiracid-2 in shellfish. As such the data provides the first published evidence for yessotoxins and azaspiracids in Argentinean shellfish and further evidence for the continuing presence of lipophilic marine toxins in Argentinean waters. Highlights: Lipophilic toxin profiles in Argentina. First detection of AZAs and YTXs. Links to human intoxication. Comparison with MBA. Profile species dependencies.